Chitosan based dielectrics for use in single walled carbon nanotube-based thin film transistors. Issue 9 (17th February 2023) - Ronnasi, Bahar; Tousignant, Mathieu N.; Lessard, Benoît H.
Abstract : Chitosan is a sustainable and solution-processable natural polyelectrolyte that can form electrical double layers at high frequencies (<1 kHz) when integrated as the dielectric in metal–insulator–metal capacitors (MIM) and thin-film transistors (TFT). Abstract : Chitosan, a sustainable biopolymer, is a naturally occurring solution processable polyelectrolyte that can form electrical double layers at high frequencies (<1 kHz) and can be integrated as the dielectric in metal–insulator–metal (MIM) capacitors and thin-film transistors (TFTs). In this study, we achieved capacitance densities as high as 11.1 nF mm −2 for the fabricated MIM capacitors. This was achieved through optimization of the chitosan content and the acid concentration of solutions during thin-film fabrication. We report the first chitosan-based TFT using semiconducting single-walled carbon nanotubes (SWCNTs). SWCNTs are emerging printable air-stable semiconductors that yield high hole mobility values in TFTs and can function at low voltages when paired with a high- k dielectric. A low- k poly-l -lactic acid (PLA) encapsulating layer was introduced between chitosan and the semiconducting channel in a top gate bottom contact architecture. The PLA layer suppresses unfavourable charge trapping phenomena between the polar hydroxyl groups of chitosan and SWCNTs as well as minimizes degradation of SWCNTs by moisture and oxygen. The PLA/chitosan devices achieved a high mobility upwards of 20 cm 2 V −1 s −1 with an on/off current ratio in the 10 4 range and a low threshold voltage of −1.6 V. The mobility values achieved in this work are 100–1000 fold greater than previously reported values for blends of chitosan, making SWCNT TFTs with a PLA/chitosan bilayer dielectric a promising dielectric for fast and low power applications within the field of printed electronics.